Developing Smart Cities: Regulatory and Policy Implications for the State of Qatar. Issue 7 (19th May 2023) - Badran, Ahmed
ABSTRACT: Smart cities represent an emerging trend that may have policy and regulatory implications for telecoms regulators in many countries including Qatar. This paper draws on a review of interdisciplinary literature on regulatory governance and smart cities besides primary data collected from interviews with telecom and urban planning experts as well as regulatory members of staff to offer illustrations of the regulatory challenges and policy implications facing the development of smart cities with special focus on the state of Qatar. The paper emphasizes that regulatory policy-makers are required to go beyond the obvious and immediate benefits of smart cities to capture the full picture of potential impacts on regulatory and policy processes. For the transition towards smart cities to be handled successfully, regulatory policy-makers are required to address the new regulatory challenges by developing proactive rather than reactive approaches in dealing with the implementation of smart city initiatives.